Spaces of the Religious Economy: Negotiating the Regulation of Religious Space in Singapore. - Woods, Orlando (Journal for the Scientific Study of Religion (John Wiley & Sons, Inc.), 2018)
Abstract: Over the past three decades, the theory of religious economy has been established, applied, debated, developed, and rejected. It has proven to be as divisive as any "general theory" of religion should be, and yet its core tenets continue to engage and unite scholars around the world. In response to broader shifts within the sociology of religion, this article reframes religious economy by advancing a spatial approach to its theorization. A spatial approach can help develop new perspectives on the regulation of religion, and the resistant agency of religious groups. With a focus on the "secular monopoly" of Singapore, it demonstrates how the restricted supply of land for religious purposes increases competition between religious groups. To overcome restrictions, religious groups pursue strategies of spatial and organizational boundary crossing. This has led to the closer regulation of space, and highlights the recursive interplay between the regulation and praxis of religion in Singapore.